2017
DOI: 10.1371/journal.pntd.0005791
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic analysis of the total and surface-exposed proteomes of Plasmodium vivax salivary gland sporozoites

Abstract: Plasmodium falciparum and Plasmodium vivax cause the majority of human malaria cases. Research efforts predominantly focus on P. falciparum because of the clinical severity of infection and associated mortality rates. However, P. vivax malaria affects more people in a wider global range. Furthermore, unlike P. falciparum, P. vivax can persist in the liver as dormant hypnozoites that can be activated weeks to years after primary infection, causing relapse of symptomatic blood stages. This feature makes P. vivax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 89 publications
6
110
0
Order By: Relevance
“…[30] A recent report used clinical samples to identify 605 P. vivax proteins from blood stages of the parasite, [31] while another used clinical samples and blood feeding of mosquitoes to identify over a thousand sporozoite stage proteins. [32] More recently, papers have increased the coverage of the P. vivax proteome to over a thousand proteins; however, this was possible only by injecting non-human primates with the parasite. [33,34] …”
Section: Proteomics Studies Have Started To Address Some Of the Gamentioning
confidence: 99%
“…[30] A recent report used clinical samples to identify 605 P. vivax proteins from blood stages of the parasite, [31] while another used clinical samples and blood feeding of mosquitoes to identify over a thousand sporozoite stage proteins. [32] More recently, papers have increased the coverage of the P. vivax proteome to over a thousand proteins; however, this was possible only by injecting non-human primates with the parasite. [33,34] …”
Section: Proteomics Studies Have Started To Address Some Of the Gamentioning
confidence: 99%
“…Protein O-fucosyltransferase 2 (POFUT2) initiates metazoan TSR Oglycosylation and plays an important role in the folding and stabilization of these proteins (12)(13)(14)(15)(16). Recently, TSR O-glycosylation has also been observed in Plasmodium falciparum and Plasmodium vivax (17,18): this O-glycan is initiated by a homologue of POFUT2 and is important for stabilizing proteins with TSR domains and efficient host infection (19). O-Glycosylation of TSR domains may also be an important consideration in vaccine design (20).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, homologs of several genes required for protein glycosylation are present and conserved in the genomes of Plasmodium spp. and metabolomic analyses of parasite material has demonstrated the presence of the nucleotide sugars required for protein glycosylation, which alluded to the existence of as yet undiscovered parasite glycans.With the aid of modern protein mass spectrometry methods, several research groups have recently tackled the issues of glycan lability and relatively small sample sizes to begin characterizing the true diversity of Plasmodium protein glycosylation [6][7][8][9][10][11][12]. Evidence for the synthesis of short N-linked glycans has been reported in asexual blood stages of Plasmodium falciparum [6], and there is every reason to expect that these modifications will be found in other life cycle stages as well.…”
mentioning
confidence: 99%
“…Evidence for the synthesis of short N-linked glycans has been reported in asexual blood stages of Plasmodium falciparum [6], and there is every reason to expect that these modifications will be found in other life cycle stages as well. Cell surface proteomic studies of P. falciparum and P. vivax sporozoites, the two species responsible for the majority of malaria cases and deaths, have demonstrated that O-and C-linked glycans exist on the essential adhesive proteins, TRAP and CSP [8,10]. These abundant surface proteins are required for parasite infectivity and are prime vaccine candidates because sporozoites represent a population bottleneck in the life cycle as parasites pass from mosquito to human and establish an infection in the liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation